Waardenburg's Syndrome - Eyıbılen, Ahmet; Bulut, Selçuk (Fırat University, 2004)
Waardenburg Syndrome (WS) is a heterogenous group of auditory-pigmentary syndromes. This disease is an autosomal dominant disorder, characterized by the combination of sensorineural hearing loss and pigmentary abnormalities. Hearing loss and other phenotypic expression is highly variable. Hearing loss usually is only finding affected the patient's life. Here we report two patients with WS Type I and one patient with WS Type II. ©2004, Fırat Üniversitesi, Tıp Fakültesi

Waardenburg Sendromu (WS) işitsel-pigmenter sendromların heterojen bir grubu olup otozomal dominant geçişlidir. Etkilenen kişilerde sensörinöral işitme kaybı ve pigmentasyon bozukluklarıyla ortaya çıkar. Işitme azlıgı ve diger fenotipik özellikler yüksek oranda degişkenlik gösterir. Işitme kaybı çogunlukla hastanın yaşamını etkileyen tek bulgudur. Bu çalışmada ikisinde WS Tip I, birinde WS Tip II tanısı konan üç hasta nedeniyle Waardenburg sendromu güncel literatür ışıgında sunuldu. ©2004, Fırat Üniversitesi, Tıp Fakültesi
Waardenburg Sendromu